Non-typeable Haemophilus influenzae major outer membrane protein P5 contributes to bacterial membrane stability, and affects the membrane protein composition crucial for interactions with the human host - Su, Yu-Ching; Kadari, Mahendar; Straw, Megan L.; Janoušková, Martina; Jonsson, Sandra; Thofte, Oskar; Jalalvand, Farshid; Matuschek, Erika; Sandblad, Linda; Végvári, Ákos; Zubarev, Roman A.; Riesbeck, Kristian (Frontiers in Cellular and Infection Microbiology, 2023)
Non-typeable Haemophilus influenzae (NTHi) is a Gram-negative human pathogen that causes a wide range of airway diseases. NTHi has a plethora of mechanisms to colonize while evading the host immune system for the establishment of infection. We previously showed that the outer membrane protein P5 contributes to bacterial serum resistance by the recruitment of complement regulators. Here, we report a novel role of P5 in maintaining bacterial outer membrane (OM) integrity and protein composition important for NTHi-host interactions. In silico analysis revealed a peptidoglycan-binding motif at the periplasmic C-terminal domain (CTD) of P5. In a peptidoglycan-binding assay, the CTD of P5 (P5CTD) formed a complex with peptidoglycan. Protein profiling analysis revealed that deletion of CTD or the entire P5 changed the membrane protein composition of the strains NTHi 3655Δp5CTD and NTHi 3655Δp5, respectively. Relative abundance of several membrane-associated virulence factors that are crucial for adherence to the airway mucosa, and serum resistance were altered. This was also supported by similar attenuated pathogenic phenotypes observed in both NTHi 3655Δp5CTD and NTHi 3655Δp5. We found (i) a decreased adherence to airway epithelial cells and fibronectin, (ii) increased complement-mediated killing, and (iii) increased sensitivity to the β-lactam antibiotics in both mutants compared to NTHi 3655 wild-type. These mutants were also more sensitive to lysis at hyperosmotic conditions and hypervesiculated compared to the parent wild-type bacteria. In conclusion, our results suggest that P5 is important for bacterial OM stability, which ultimately affects the membrane proteome and NTHi pathogenesis.